2022
DOI: 10.1590/1981-5271v46.4-20210459
|View full text |Cite
|
Sign up to set email alerts
|

Atitude perante a morte e opinião de estudantes de Medicina acerca da formação no tema

Abstract: Resumo: Introdução: Atualmente, a maioria das pessoas está inserida num contexto sócio-histórico de negação da morte, incluindo médicos que lidam com o morrer diariamente que se consideram despreparados perante a morte de um paciente. O desconforto desses profissionais nesse processo de morte deve-se em parte à deficiência da formação ocorrida durante a graduação. Objetivo: Este estudo teve como objetivos analisar a opinião dos alunos de Medicina da Faculdade Pernambucana de Saúde (FPS) acerca da abordagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
(16 reference statements)
2
1
0
12
Order By: Relevance
“…In this context, from an academic point of view, the participants reported that classroom discussions about coping with death occurred only occasionally and that the theoretical and practical content offered was insufficient. These findings are in line with previous studies 20,[26][27][28] , which demonstrated that teaching-learning experiences on this subject during undergraduate studies are scarce.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this context, from an academic point of view, the participants reported that classroom discussions about coping with death occurred only occasionally and that the theoretical and practical content offered was insufficient. These findings are in line with previous studies 20,[26][27][28] , which demonstrated that teaching-learning experiences on this subject during undergraduate studies are scarce.…”
Section: Discussionsupporting
confidence: 93%
“…Although most students consider that "death is part of life," "it is a natural process" that represents "the end of a cycle," when analyzing the feelings related to the end-of-life process, in line with previous studies, conflicting feelings and negative emotions were observed, such as sadness, distress, longing, suffering, anxiety and pain 16,19,20,26 . This behavior may be associated with a defense mechanism, used to minimize the fear of death and the difficulty in coping with it 19 .…”
Section: Discussionsupporting
confidence: 57%
“…Vale ressaltar que, em um estudo feito na Faculdade Pernambucana de Saúde (FPS), constatou-se que os acadêmicos de medicina associam o processo de morrer com sentimentos negativos, os quais, em ordem crescente, são o medo, a tristeza, a angústia e a conformação. Paralelo a isto, os estudantes compreendem a importância da discussão sobre a temática durante a graduação, já que consideram que o debate da mesma possui impacto direto no exercício da futura profissão (21) .…”
Section: Resultsunclassified
“…Neste sentido, o estigma da morte delineia as habilidades médicas, as quais ficam restritas à carência de conhecimento advindos da graduação. O profissional, portanto, não se sente com preparo suficiente para dar suporte paliativo ao paciente e sua família (21) .…”
Section: Resultsunclassified
See 1 more Smart Citation